Ensilabilidade da gramínea tropical Splenda - Martins, J.M. (1998)
This study was done to evaluate the ensilability of the tropical grass Splenda (Setaria sphacelata var. sericea x S. sphacelata var. splendida) and the effect of several treatments on the characteristics and quality of the silage obtained. Irrigated grass was chopped ( 4 cm) and submitted to four treatments prior to ensiling: control treatment (chopped green grass) (T1); 24 h pre-wilted grass (T2); green grass with 85% formic acid (4 l ADD-F®/t); and green grass with Ecosyl® (7.5 g/t). Results showed that T4 was the best treatment. T1, T2 and T3 presented worse results, with higher values of pH, ammonia nitrogen, NDF and ADF and lower values of lactic acid and in vitro dry matter and organic matter digestibility.